2022
DOI: 10.25073/2588-1132/vnumps.4384
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics and Value of Multislice Computed Tomography in the Diagnosis of Acute Appendicitis

Abstract: Objectives: This study was done to describe the imaging characteristics of acute appendicitis on multislice computed tomography (MSCT) and the value of MSCT scan in the diagnosis of acute appendicitis. Methods: The study used retrospective and cross-sectional methods to analyze the results of 117 patients who were taken photos of CT at E Hospital from February 2021 to November 2021. Results: The most common age was over 50 years old, and the average age was 40.1±20.8. The ratio of male/female was 1/1.25. Locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Yun et al reported a sensitivity of 96.40% and a specificity of 92.17% for standard-dose CT scans [ 10 ]. Doan et al reported a higher sensitivity (97.4%) and accuracy (96.6%) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yun et al reported a sensitivity of 96.40% and a specificity of 92.17% for standard-dose CT scans [ 10 ]. Doan et al reported a higher sensitivity (97.4%) and accuracy (96.6%) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appendicitis is one of the most common causes of acute abdomen in adults and has a lifetime risk of 6%-7% [ 1 ]. It is defined as inflammation of the vermiform appendix, an acute condition that presents within 24 hours [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations